Illumina-based transcriptomic analysis of the fast-growing leguminous tree Acacia crassicarpa: functional gene annotation and identification of novel SSR-markers - Ishio, Shougo; Kusunoki, Kazutaka; Nemoto, Michiko; Kanao, Tadayoshi; Tamura, Takashi (Frontiers in Plant Science, 2024)
Acacia crassicarpa is a fast-growing leguminous tree that is widely cultivated in tropical areas such as Indonesia, Malaysia, Australia, and southern China. This tree has versatile utility in timber, furniture, and pulp production. Illumina sequencing of A. crassicarpa was conducted, and the raw data of 124,410,892 reads were filtered and assembled de novo into 93,317 unigenes, with a total of 84,411,793 bases. Blast2GO annotation, Benchmark Universal Single-Copy Ortholog evaluation, and GO-term classification produced a catalogue of unigenes for studying primary metabolism, phytohormone signaling, and transcription factors. Massive transcriptomic analysis has identified microsatellites composed of simple sequence repeat (SSR) loci representing di-, tri-, and tetranucleotide repeat units in the predicted open reading frames. Polymorphism was induced by PCR amplification of microsatellite loci located in several genes encoding auxin response factors and other transcription factors, which successfully distinguished 16 local trees of A. crassicarpa tested, representing potentially exploitable molecular markers for efficient tree breeding for plantation and biomass exploitation.